2016
DOI: 10.2334/josnusd.15-0607
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical agenesis of the mandibular third molars and agenesis of other teeth in a Japanese orthodontic population

Abstract: This study was conducted to investigate the association between symmetrical agenesis of the mandibular third molars and agenesis of other teeth in Japanese orthodontic patients. A sample of 64 patients with symmetrical agenesis of the mandibular third molars and without agenesis of the maxillary third molars was selected as the third molar agenesis group. In addition, 585 patients with all 4 third molars were selected as controls. The main materials examined for diagnosis of tooth agenesis were panoramic radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
1
11
0
3
Order By: Relevance
“…This minimum age of 14 years was based on the suggestion of Garn and Lewis [ 7 ] that the upper age limit for M3 agenesis is 14 years. Some studies have adopted a maximum age of 21 years [ 2 , 22 , 23 ]. The adaptation is based on the fact that eruption of M3s begins at 14–21 years of age [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This minimum age of 14 years was based on the suggestion of Garn and Lewis [ 7 ] that the upper age limit for M3 agenesis is 14 years. Some studies have adopted a maximum age of 21 years [ 2 , 22 , 23 ]. The adaptation is based on the fact that eruption of M3s begins at 14–21 years of age [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 Likewise, studies conducted by Hirakata et al and Sanpei et al has shown association between agenesis of any other teeth when there was presence of bilateral agenesis of mandibular or maxillary third molars. 22,23 Regarding the limitation of the study, one major concern with this study is the lack of random sampling, which was avoided to prevent unnecessary radiographic exposure to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Na rycinie 5 przedstawiono zastosowanie autotransplantacji górnych M3 w leczeniu agenezji PM2 w żuchwie. Istotne ograniczenie może dodatkowo stanowić stosunkowo wysoka częstość występowania agenezji M3 (20-30%) (26) oraz współistniejąca agenezja innych zębów (75)(76)(77)(78)(79).…”
Section: Forumunclassified